Use of Enhanced Recovery after Surgery (ERAS) in Major Gynecologic Surgery [1R]. (May 2018) - Owens, Kristin; Stovall, Dale W.
Abstract : INTRODUCTION: The enhanced recovery after surgery protocol (ERAS) is a postoperative protocol which emphasizes quality of recovery over speed. Our study compared postoperative antiemetic and opioid use before and after implementation of the ERAS program at MDMC. METHODS: In this single-center, cohort study, we identified two groups of patients for comparison. The first group was women who underwent a major gynecologic surgical procedure 6 months prior to ERAS implementation and the second group were women who underwent their procedure in the six months after implementation. Major gynecologic procedures included TAH, TVH, myomectomy, and open staging procedures. Primary outcomes were post-op anti-emetic and opioid therapy. Secondary outcomes included intraoperative i.v. fluids and length of stay (LOS). RESULTS: A total of sixty subjects were included in the study, 29 in the pre-ERAS group and 31 in the post-ERAS group. The mean age of the study population was 49.5. There were no differences between groups in regards to post-operative anti-emetic use. A significantly greater proportion of subjects in the post-ERAS group, none of whom received PCA administration, received i.v. opioids on the ward, 25.8% (8/31) versus 6.9% (2/29), respectively (P < 0.05). The post-ERAS group also received significantly less intraoperative i.v. fluids, 1595.9 mL versus 1909.5 mL, respectively (P < 0.05). The LOS was less for the post-ERAS group, 2.0 days versus 2.5 days, but the difference was not significant. CONCLUSION: Implementation of ERAS for major gynecologic procedures at Methodist significantly reduced i.v. fluid use, but did not reduce the need for anti-emetic or opioid therapy.